FINDINGS FROM AN EXPEDITION INVESTIGATING EPIGRAPHIC AND ARCHITECTURAL MONUMENTS IN THE VILLAGE OF SHAKHUVA (LAKSKY REGION, REPUBLIC OF DAGESTAN) - Kurbanov, Ahmed Dzabrailovic; Kaaev, Il'as Abdulmezidovic (History, Archeology and Ethnography of the Caucasus, 2024)
The article focuses on the examination of epigraphic and architectural monuments in the village of Shakhuva, located in the Laksky region of the Republic of Dagestan. It presents, for the first time, epigraphic materials dating back to the 18th–19th centuries, shedding light on specific aspects of the social and political history of the region’s development. These materials include tombstones bearing the emblem of the Shamkhal, indicative of the presence of authoritative figures within the society, as well as the graves of village residents who perished during the 1877 uprising in Dagestan. Notably, among these graves is that of Shagmilav, a prominent leader of the Tsudahar battle and a key imam serving under Shamil during the Caucasian War. The analysis extends to architectural features, notably the partially preserved Kyulla-mizit mosque, which served additional functions and was once situated outside the settlement. This mosque facilitated complete ritual ablution (ghusl) for men. Also examined is a structure positioned atop a steep rocky ridge above the village, resembling a tower externally and offering panoramic views of the Kazikumukhskoye Koisu River valley. The article presents arguments regarding the origins of the toponym “Shahuva,” suggesting its early form as “Shaku” or “Shahu.”
Keywords: Dagestan; Laksky region; Shakhuva; tombstones; Shamkhal emblem; naib; mosque; tower